Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Melalui Model Guided Inquiry - Ernawati, Ernawati; Sari, Tri Maniarta; Haris, Iyan Nurdiyan (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
The implementation of a learning model has a big role in developing students' critical thinking skills. One of the learning models that can be used is the guided inquiry model which involves students in investigating and exploring certain topics or problems with guidance and support from teachers or facilitators. The application of the guided inquiry model is equipped with a Learner Activity Sheet that guides the guided inquiry steps during learning and is assisted by an IT-based learning media platform (google classroom) to facilitate communication and collaboration during the implementation of guided inquiry to be more effective and efficient. This research is a Quasi Experiment research with Nonequivalent Control Group design. The research sample consisted of experimental class (22 students) and control class (21 students). Critical thinking skills data were obtained through post test and analyzed descriptively quantitatively and inferential statistical analysis with the Independent sample t-test test. Based on the results of descriptive tests, it is known that the critical thinking skills of students in the experimental class have an average value of 75.79 (high category) and the control class is 64.98 (medium category) and inferential statistical analysis using the Independent sample t-test test obtained a sign value of 0.0000.05. Thus it is concluded that the application of the guided inquiry model in learning biology in high school with the Learner Activity Sheet and assisted by an IT-based learning media platform (google classroom) has a positive effect on improving students' critical thinking skills.